Influence of fluoride ion on the performance of PCE in hemihydrate gypsum pastes. (1st April 2022) - Qi, Huahui; Ma, Baoguo; Tan, Hongbo; Su, Ying; Lu, Wenda; Jin, Zihao
Abstract: Impurities in phosphogypsum have a significant impact on its properties and the performance of admixture. This study aims to reveal the influence of fluoride ion (F − ) on the performance of polycarboxylate superplasticizer (PCE) in hemihydrate gypsum pastes. By introducing F − into the natural hemihydrate gypsum - PCE system, workability, mechanical properties, and hydration process were systematically studied. The results showed that F − had a negative effect on the fluidity of PCE plasticized hemihydrate gypsum pastes. Moreover, F − significantly reduced the setting time regardless of the presence or absence of PCE. It was found that CaF2 with low solubility was preferentially formed to CaSO4 ⋅2H2 O and served as nuclei to promote the hydration of hemihydrate gypsum. The adsorption behavior of PCE on the surface of CaF2 consumed PCE, resulting in the decline of dispersion ability. Highlights: F − negatively influenced the workability of hemihydrate pastes plasticized by PCE. In the presence of F −, the formation of CaF2 was preferential to CaSO4 ⋅2H2 O. CaF2 acted as nuclei to promote gypsum hydration. PCE was consumed due to the adsorption on the surface of CaF2 .